A method for preparing high-performance CsPbI2Br perovskite solar cells
Patent Information
- Application Number
- CN202611253264.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
1、体相缺陷密度高,非辐射复合严重:溶液结晶过程易产生大量铅空位、未配位Pb2+、卤素空位等体相与晶界缺陷,形成深能级复合中心,诱发严重的载流子非辐射复合,大幅降低器件光电转换效率
本发明通过添加Cr(acac)3优化CsPbI2Br吸光层,制备出高效稳定的碳基全无机CsPbI2Br PSCs。Cr3+在钙钛矿晶格部分取代Pb2+,而acac−则在钙钛矿晶界处与未配对的Pb2+形成强键合,从晶格和晶界两个方面有效地钝化了CsPbI2Br钙钛矿薄膜的的体相缺陷。此外,引入Cr(acac)3调整了CsPbI2Br钙钛矿吸收层的能级,使其更好地与碳层的能级匹配,抑制空穴载流子的复合。当添加Cr(acac)3浓度为0.1mg/mL时,制备出的碳基全无机CsPbI2BrPSCs实现了14.21%的最佳PCE,VOC为1.22V,FF为78.45%。在相对湿度约为15~20%的环境中,添加Cr(acac)3后的未封装CsPbI2Br PSCs存放40天,仍能保持初始效率的92%以上,表现更优异的稳定性。
Smart Images

Figure CN122995321A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell technology, and specifically to a method for preparing high-performance CsPbI2Br perovskite solar cells. Background Technology
[0002] Over the past decade or so, perovskite solar cells (PSCs) have demonstrated enormous potential for photovoltaic applications, with their photoelectric conversion efficiency increasing from an initial 3.8% to 27.3% thanks to their superior photoelectric performance. Traditional organic-inorganic hybrid perovskites, using methylamine (MA) as a base... + ), formamidin (FA) + As an A-site organic cation, although it has excellent photoelectric properties, organic cations are prone to decomposition and volatilization in high temperature and humid environments, resulting in poor damp-heat stability of the device, which seriously restricts its industrialization.
[0003] To address this pain point, the industry is using cesium ions (Cs) + A fully inorganic substitution strategy was adopted to develop the CsPbI2Br fully inorganic perovskite system. This material has a suitable photovoltaic bandgap and excellent intrinsic thermal stability, and is the current research system for wide bandgap stable photovoltaic devices.
[0004] To address the common industry-wide problems of high defect density and poor crystallinity in CsPbI₂Br thin films prepared by solution methods, a relatively mature existing technology is the acetylacetone metal compound precursor doping modification technique, which utilizes the acetylacetone group (acac - Lilliputian base properties with lone pairs of electrons, coordinating and passivating uncoordinated lead defects at perovskite grain boundaries, and simultaneously modulating the lattice structure through metal ion doping, represent the optimal modification route currently available that balances low cost, ease of preparation, and high efficiency. The relevant existing core technologies are as follows: (1) Samarium-based acetylacetone doping modification scheme: Yang et al. used samarium acetylacetone (Sm(acac)3) as a CsPbI2Br perovskite additive, utilizing Sm 3+ Partially substituted lattice Pb 2+ This achieves a slight lattice shrinkage, while simultaneously coordinating with aacac - By passivating NiOx / perovsk interface defects and optimizing thin film crystallization properties, the optimal photoelectric conversion efficiency of the doped device can reach 12.86%. This approach can effectively reduce interface recombination and slightly improve device efficiency, and is currently the most representative acetylacetone metal modification technology for inorganic wide bandgap perovskites.
[0005] (2) Gallium-based and aluminum-based acetylacetone doping modification schemes: Existing public research has confirmed that group III metal acetylacetone compounds can achieve perovskite crystallization regulation and defect passivation. Among them, gallium acetylacetone (Ga(acac)3), as a typical trivalent metal-organic additive, can effectively regulate the nucleation and growth process of perovskite, reduce the density of trapped states in the thin film, prolong the carrier lifetime, and significantly improve the moisture resistance of the device. Aluminum acetylacetone (Al(acac)3) can be enriched at grain boundaries and thin film surfaces during the perovskite crystallization process, effectively releasing lattice micro-strain, increasing thin film density, reducing pinholes and bulk defects, and improving carrier transport characteristics.
[0006] (3) Cadmium-based acetylacetone doping modification scheme: In the existing technology, divalent metal acetylacetone salts can achieve perovskite vacancy filling and energy level fine-tuning. Cadmium acetylacetone (Cd(acac)2) can utilize Cd... 2+ Its ion compatibility advantage fills lead vacancies within the CsPbI2Br lattice, while relying on acac - Functional group coordination passivates unsaturated lead defects at grain boundaries, improves the crystallization quality of thin films, and can moderately optimize the energy level matching of the electron transport layer / perovskite interface, reducing interface charge recombination loss.
[0007] In summary, the closest existing technical solution to this invention is: using acetylacetone metal compounds such as Sm(acac)3, Ga(acac)3, Al(acac)3, and Cd(acac)2 as perovskite precursor additives, relying on metal ion lattice doping, acac - The dual role of grain boundary coordination enables defect passivation and crystallization regulation, thereby improving the photoelectric performance of perovskite solar cells. This technology is widely applicable to all-inorganic and hybrid perovskite photovoltaic systems and is currently the mainstream and mature solution for defect engineering.
[0008] The industry generally adopts Cs + Inorganic CsPbI₂Br perovskite solar cells can be fabricated by doping or completely replacing organic components with inorganic cations. This system possesses advantages such as excellent thermal stability and bandgap suitability for photovoltaic applications, making it a research hotspot for wide-bandgap perovskite solar cells. However, existing solution-based CsPbI₂Br perovskite films have significant technical drawbacks, as follows: 1. High bulk defect density and severe non-radiative recombination: The solution crystallization process easily generates a large number of lead vacancies and uncoordinated Pb. 2+ Bulk phase and grain boundary defects such as halogen vacancies form deep-level recombination centers, inducing severe nonradiative recombination of charge carriers and significantly reducing the photoelectric conversion efficiency of devices.
[0009] 2. Poor crystal structure stability and easy to undergo phase transition failure: The high defect state of CsPbI2Br perovskite has high lattice stress and is prone to irreversible phase transition under light and humid heat environment, which leads to the decay of thin film optical activity and a significant decrease in the long-term stability of the device.
[0010] 3. Poor energy level matching and high carrier transport loss: The energy level matching between pure CsPbI2Br perovskite and carbon-based electrode is poor, resulting in a high potential barrier during charge transport and severe carrier recombination loss, which limits the improvement of battery open-circuit voltage and fill factor.
[0011] 4. Existing metal acetylacetone additive modification systems are imperfect: Current research mostly uses metal acetylacetone compounds such as Sm(acac)3, Ga(acac)3, Al(acac)3, and Cd(acac)2 to modify perovskites, but their ion size and coordination characteristics are limited, and they cannot simultaneously achieve lattice defect repair, grain boundary passivation, and interface energy level regulation. Summary of the Invention
[0012] The purpose of this invention is to provide a method for preparing high-performance CsPbI2Br perovskite solar cells. The cell of this invention has an all-inorganic carbon-based structure of FTO / TiO2 electron transport layer / Cr(acac)3-doped CsPbI2Br perovskite light-absorbing layer / carbon electrode, which abandons traditional organic hole transport materials. The preparation process is simple, low-cost and has excellent stability.
[0013] The technical solution of the present invention: A method for preparing high-performance CsPbI2Br perovskite solar cells includes the following steps: S1, TiO2 electron transport layer preparation: Titanium tetrachloride was dissolved in deionized water under ice bath conditions to prepare TiO2 precursor solution; FTO glass after cleaning and UV ozone treatment was immersed in TiO2 precursor solution, deposited at constant temperature, and annealed to obtain TiO2 electron transport layer. S2. Preparation of the perovskite light-absorbing layer: Prepare a Cr(acac)3 and DMSO modified solution, add PbBr2, PbI3 and CsI, stir until clear, and obtain a modified perovskite precursor solution; The modified perovskite precursor solution was preheated and then spin-coated onto the TiO2 electron transport layer using a two-step spin-coating process. After pre-annealing and high-temperature annealing, a Cr(acac)3-doped CsPbI2Br perovskite thin film was prepared. S3. Carbon electrode preparation: Carbon paste is coated onto the surface of a Cr(acac)3-doped CsPbI2Br perovskite thin film using a screen printing process, and then cured by heating to complete the preparation of the CsPbI2Br perovskite solar cell.
[0014] Preferably, in step S1, the volume ratio of titanium tetrachloride to deionized water is 9:400. The FTO conductive glass was cleaned with detergent during the cleaning process. Then, the cleaned FTO conductive glass was placed in distilled water and ethanol for ultrasonic cleaning for 20-30 minutes each, and then dried at 60℃ for 30 minutes. During the ultraviolet ozone treatment of FTO glass: the intensity of ultraviolet light is 0.4mW / cm², ozone cleaning is performed under ultraviolet light irradiation, and the ozone cleaning time is 15-25 minutes.
[0015] Preferably, in step S1, the temperature at which the FTO glass is immersed in the TiO2 precursor solution for deposition is 60-80°C, and the deposition time is 20-40 min. The annealing time is 60-90 minutes, and the annealing temperature is 180-220℃.
[0016] Preferably, in step S2, the concentration of Cr(acac)3 and DMSO modified solution is 0.05 mg / mL to 0.15 mg / mL.
[0017] Preferably, in step S2, the solid-liquid ratio of DMSO, PbBr2, PbI, and CsI in the modified perovskite precursor solution is 100mL:22g:28g:31g.
[0018] Preferably, the preheating temperature of the modified perovskite precursor solution in step S2 is 60°C. The two-step spin coating process is as follows: the TiO2 electron transport layer is placed on a spin coater, and the preheated modified perovskite precursor solution is spin-coated onto the TiO2 electron transport layer using a pipette; spin coating is performed at 700 rpm for 5 seconds and at 4000 rpm for 35 seconds. 47 μL of modified perovskite precursor solution was used for a 1 cm * 1 cm TiO2 electron transport layer.
[0019] Preferably, the pre-annealing temperature in step S2 is 36-40℃, and the pre-annealing time is 70-90s; The high-temperature annealing temperature is 160-200℃, and the high-temperature annealing time is 5-15 minutes.
[0020] Preferably, the screen printing process in step S3 is as follows: carbon paste is coated onto the surface of a highly Cr(acac)3-doped CsPbI2Br perovskite thin film by screen printing, and heated on a heating stage at 110-140℃ for 10-20 minutes to complete the preparation of CsPbI2Br perovskite solar cell.
[0021] Preferably, the solid content of the carbon slurry in step S3 is 50 wt%; The coating thickness of carbon paste on the surface of highly Cr(acac)3-doped CsPbI2Br perovskite thin films was controlled at 8-10 μm.
[0022] Preferably, in step S3, carbon paste is screen-printed onto the surface of a highly Cr(acac)3-doped CsPbI2Br perovskite film and heated on a heating stage at 120°C for 15 minutes.
[0023] The core modification mechanism of this invention: utilizing the bifunctional modification properties of Cr(acac)3, Cr with a smaller radius... 3+ Lead is introduced into the perovskite lattice through interstitial doping or partial substitution to fill lead vacancies, regulate lattice stress, and stabilize the crystal structure. - The group utilizes oxygen lone pair electrons to interact with uncoordinated Pb at the grain boundary. 2+ Strong coordination passesivates deep-level defects at grain boundaries; at the same time, Cr(acac)3 doping optimizes the interface energy level alignment between perovskite and carbon electrode, reducing the charge transport barrier.
[0024] The beneficial effects of this invention are: This invention optimizes the CsPbI₂Br light-absorbing layer by adding Cr(acac)₃, thus preparing highly efficient and stable carbon-based all-inorganic CsPbI₂Br PSCs. 3+ Partial substitution of Pb in the perovskite lattice 2+ , and acac − Then at the perovskite grain boundaries, unpaired Pb 2+ Strong bonding was formed, effectively passivating bulk defects in the CsPbI₂Br perovskite film from both lattice and grain boundary perspectives. Furthermore, the introduction of Cr(acac)₃ adjusted the energy levels of the CsPbI₂Br perovskite absorber layer, allowing for better matching with the energy levels of the carbon layer and suppressing hole carrier recombination. When the concentration of Cr(acac)₃ added was 0.1 mg / mL, the prepared carbon-based all-inorganic CsPbI₂Br PSCs achieved an optimal PCE of 14.21%. V OC The voltage is 1.22V and the FF is 78.45%. In an environment with a relative humidity of about 15~20%, the unencapsulated CsPbI2Br PSCs with added Cr(acac)3 can still maintain more than 92% of the initial efficiency after 40 days of storage, showing better stability. Attached Figure Description
[0025] Figure 1 XRD patterns of perovskite films with different concentrations of Cr(acac)3 added; Figure 2XPS spectra of comparative and Cr(acac)3-added perovskite films: (a) O 1s, (b) Pb 4f, (c) Cs 3d, (d) I 3d and (e) Br 3d; Figure 3 SEM images of comparative perovskite films; Figure 4 SEM image of the perovskite film after adding Cr(acac)3; Figure 5 EDS energy spectrum of perovskite film after adding Cr(acac)3; Figure 6 JV curves of the devices after adding different concentrations of Cr(acac)3; Figure 7 The device's EQE spectrum and integrated current density plot; box plot of JV curve parameters for 20 PSCs: Figure 8 The PCE diagram of the device; Figure 9 The diagram shows the VOC, JSC, and FF values of the device. Figure 10 The diagram shows the stable current output and stable efficiency output of the device after adding Cr(acac)3, as well as the comparative example. Figure 11 This is a stability diagram of the device under room temperature conditions. Detailed Implementation
[0026] This invention provides a method for preparing high-performance CsPbI2Br perovskite solar cells. By limiting the precise doping concentration of Cr(acac)3, standardizing precursor formulation, and employing thin-film fabrication processes, a high-efficiency and high-stability all-inorganic perovskite photovoltaic device can be stably fabricated. The following detailed and reproducible description of the technical solution of this invention is provided through specific embodiments and comparative examples.
[0027] Specifications of reagents and equipment used in this invention are uniformly defined as follows: Titanium tetrachloride (analytical grade, Sinopharm Group), lead iodide (PbI2, 99.99%, Aladdin), lead bromide (PbBr2, 99.99%, Aladdin), cesium iodide (CsI, 99.99%, Aladdin), chromium acetylacetone (Cr(acac)3, 98%, Maclean), dimethyl sulfoxide (DMSO, ultra-dry solvent, 99.9%, Aladdin), FTO conductive glass (1cm*1cm, resistance 15Ω), carbon paste (commercial photovoltaic-grade carbon paste, brand: MATERWIN, CAS: 7440-4-0); preparation equipment included: programmable spin coater, high-precision constant temperature heating stage, ultraviolet ozone cleaner, ice bath reaction device, glove box (water and oxygen content <0.1 ppm); testing equipment included: solar simulator (AM 1.5G), electrochemical workstation, ultraviolet-visible spectrophotometer and steady-state fluorescence spectrometer.
[0028] Comparative example (blank control group: no Cr(acac)3 doping) This comparative example prepares a pure CsPbI2Br all-inorganic carbon-based perovskite solar cell without any Cr(acac)3 doping. Except for the absence of Cr(acac)3 additive, the other raw material ratios, process parameters, preparation environment, and testing conditions are completely consistent with the examples, serving as the benchmark sample for this invention. The specific steps are as follows: FTO substrate pretreatment: The FTO conductive glass was ultrasonically cleaned sequentially with detergent, deionized water, and anhydrous ethanol, with each ultrasonic cleaning session lasting 25 minutes. After cleaning, it was dried with nitrogen and then placed in an ultraviolet ozone cleaner for 20 minutes to remove organic impurities and residual oil from the surface.
[0029] Preparation of TiO2 electron transport layer: Under 0 ℃ ice bath conditions, 4.5 mL of titanium tetrachloride was slowly added dropwise to 200 mL of deionized water, and the mixture was stirred at low speed until the solution was clear and transparent to prepare a TiO2 precursor solution; the pretreated FTO glass was completely immersed in the TiO2 precursor solution and deposited at 70 ℃ for 30 min; after deposition, the sample was taken out, air-dried naturally, placed on a 200 ℃ constant temperature heating table for annealing for 1 h, and then naturally cooled to room temperature to obtain a dense and uniform TiO2 electron transport layer.
[0030] Preparation of pure CsPbI2Br perovskite precursor solution: In a glove box with water and oxygen content <0.1 ppm, accurately weigh 0.2202 g PbBr2, 0.2766 g PbI2, and 0.3118 g CsI, place them in a sealed sample bottle, add 1 mL of ultra-dry DMSO solvent, seal, and stir at 60 ℃ until the solid is completely dissolved and the solution is clear and transparent to obtain pure CsPbI2Br perovskite precursor solution.
[0031] Spin-coating and annealing of pure perovskite thin films: The prepared pure CsPbI2Br perovskite precursor solution was preheated on a 60 ℃ heating stage for 10 min; the TiO2 electron transport layer (FTO glass substrate loaded with TiO2) was fixed on a spin coater, and 47 μL of pure CsPbI2Br perovskite precursor solution was uniformly dropped onto the surface of the TiO2 electron transport layer. A two-step spin-coating process was adopted: low-speed spin-coating at 700 rpm for 5 s, and high-speed spin-coating at 4000 rpm for 35 s. After spin-coating, the film was immediately placed on a 38 ℃ hot plate for pre-annealing for 80 s, and then heated to 180 ℃ for constant-temperature annealing for 10 min. After natural cooling to room temperature, pure CsPbI2Br perovskite thin films were obtained.
[0032] Carbon electrode preparation: Commercial photovoltaic carbon paste was uniformly coated onto the surface of a pure perovskite film using screen printing, with the coating thickness controlled at 8-10 μm. The sample was then placed on a 120 ℃ constant temperature heating stage for 15 min to complete the preparation of the blank control group perovskite solar cell.
[0033] Device testing conditions: All samples were tested for photoelectric performance under ambient temperature, atmospheric conditions, and AM 1.5G standard sunlight, with a light intensity of 100 mW·cm². -2 The effective area tested was 0.044 cm². Five parallel samples were prepared for each group of samples, and the average value was taken as the final performance data.
[0034] The final performance of the comparative device is as follows: the photoelectric conversion efficiency (PCE) is 12.50%, the open-circuit voltage (VOC) is 1.18 V, the fill factor (FF) is 77.15%, the device has high defect density, severe non-radiative recombination of charge carriers, and poor long-term damp heat stability. Example
[0035] Preparation of the TiO2 electron transport layer (ETL): First, the FTO conductive glass was cleaned with detergent. Then, the cleaned FTO conductive glass was ultrasonically cleaned in distilled water and ethanol for 25 min each, followed by drying at 60℃ for 30 min. Next, the FTO glass was subjected to ultraviolet ozone cleaning for 20 min, with an ultraviolet light intensity of 0.4 mW / cm². The treated FTO glass was then immersed in a TiO2 precursor solution (prepared by slowly adding 4.5 mL of titanium tetrachloride to 200 mL of deionized water under 0℃ ice bath conditions, with continuous low-speed stirring until the solution became clear and transparent), and deposited at 70℃ for 30 min. After deposition, the FTO conductive glass with deposited TiO2 was annealed on a heating stage at 200℃ for 1 hour to obtain the TiO2 electron transport layer.
[0036] Preparation of the perovskite light-absorbing layer: 0.2202 g PbBr2, 0.2766 g PbI2, and 0.3118 g CsI were added to 1 mL of Cr(acac)3 and DMSO modified solutions of different concentrations (0.05, 0.10, 0.15 mg / mL). The prepared modified perovskite precursor solution was preheated at 60 °C on a heating stage. Then, the TiO2 electron transport layer was placed on a spin coater, and 47 μL of the preheated modified perovskite precursor solution was spin-coated onto it by a pipette. The spin coating was performed at 700 rpm for 5 s and at 4000 rpm for 35 s. Then, the layer was pre-annealed at 38 °C for 80 s and then annealed at 180 °C for 10 min to form a Cr(acac)3-doped CsPbI2Br perovskite film.
[0037] Preparation of carbon electrode: Two layers of carbon paste with a solid content of 50 wt% were coated on the surface of Cr(acac)3-doped CsPbI2Br perovskite film by screen printing with a 200-mesh screen (coating thickness controlled at 8-10 μm). The film was heated on a heating stage at 120 ℃ for 15 min to complete the preparation of CsPbI2Br perovskite solar cell.
[0038] Example 1 (Low concentration doping: 0.05 mg / mL Cr(acac)3) In this embodiment, a 0.05 mg / mL Cr(acac)3 and DMSO solution was used to modify the CsPbI2Br perovskite precursor by doping. The substrate pretreatment, TiO2 preparation, thin film spin coating, annealing process, electrode preparation and testing conditions were completely consistent with the comparative example. The only difference was the introduction of a low concentration of Cr(acac)3 additive into the perovskite precursor solution.
[0039] 1. Preparation of Cr(acac)3 and DMSO modified solution: Accurately weigh an appropriate amount of Cr(acac)3 solid powder, and use ultra-dry DMSO solvent to prepare a Cr(acac)3 and DMSO modified solution with a concentration of 0.05 mg / mL. Stir at room temperature in the dark for 20 min until completely dissolved.
[0040] 2. Preparation of modified perovskite precursor solution: Accurately weigh 0.2202g PbBr2, 0.2766g PbI2, and 0.3118g CsI in a glove box, add 1 mL of 0.05 mg / mL Cr(acac)3 and DMSO solution, and stir until the solution is clear and transparent to obtain a low-concentration modified perovskite precursor solution.
[0041] 3. Device fabrication: The device was fabricated using the same spin coating, pre-annealing, high-temperature annealing, and carbon electrode printing and curing process as the comparative example, resulting in a 0.05 mg / mL Cr(acac)3-doped CsPbI2Br perovskite solar cell.
[0042] The device performance in this embodiment is as follows: the photoelectric conversion efficiency (PCE) is 13.44%, the open-circuit voltage (VOC) is 1.21 V, and the fill factor (FF) is 75.26%. Compared with the blank control group, the film defect density is slightly reduced and the crystal quality is slightly improved. However, due to the low doping concentration, the effect of lattice defect repair and energy level optimization is limited, and the performance improvement is small.
[0043] Example 2 (Optimal doping concentration: 0.10 mg / mL Cr(acac)3) This embodiment uses the optimal doping concentration of 0.10 mg / mL Cr(acac)3 and DMSO modified solution as defined in this invention, which is the core preferred embodiment. All preparation processes, parameters, and test conditions are consistent with the comparative example and Example 1 above.
[0044] Device fabrication: Standardized spin coating, segmented annealing, and carbon electrode curing were used to fabricate the complete device. At this doping concentration, trace amounts of Cr... 3+ Uniformly integrated into the perovskite lattice, precisely filling lead vacancies and regulating lattice stress, acac⁻ fully passivates uncoordinated lead defects at grain boundaries, while precisely optimizing the energy level matching at the perovskite / carbon electrode interface, achieving the optimal effect of triple synergistic modification.
[0045] The optimal performance of the device in this embodiment is as follows: photoelectric conversion efficiency (PCE) of 14.21%, open-circuit voltage (VOC) of 1.22 V, and fill factor (FF) of 78.45%. The thin film is densely crystalline with no pinholes, and non-radiative recombination of charge carriers is significantly suppressed. The device's stability under damp heat and light is greatly improved, making it the optimal implementation process for this invention.
[0046] Example 3 (High concentration doping: 0.15 mg / mL Cr(acac)3) This embodiment uses an over-range, high-doping concentration of 0.15 mg / mL Cr(acac)3 and DMSO modified solution to verify the optimal range of parameters in this invention. The preparation process and testing standards are the same as in Example 1.
[0047] The device performance in this embodiment is as follows: the photoelectric conversion efficiency (PCE) is 13.67%, the open-circuit voltage (VOC) is 1.21 V, and the fill factor (FF) is 76.98%. Compared with the optimal embodiment 2, the excessive Cr(acac)3 doping amount leads to the aggregation of trace metal ions and the accumulation of organic components at grain boundaries, which slightly hinders carrier transport and introduces a small number of new interface defects. The device performance has declined, proving that the modification effect decreases after the doping concentration exceeds the preferred range of this invention.
[0048] To analyze the effect of Cr(acac)3 as a perovskite precursor additive on the crystal growth of CsPbI2Br perovskite thin films, XRD tests were performed, such as... Figure 1 As shown (corresponding to the parallelogram, Examples 1, 2, and 3). The control CsPbI₂Br film exhibits two diffraction peaks at approximately 14.60° and 29.50°, representing the (100) and (200) crystal planes of the cubic phase of CsPbI₂Br, respectively. However, with increasing Cr(acac)₃ concentration, the diffraction peaks of the CsPbI₂Br perovskite film shift slightly to higher angles, reaching their strongest when the Cr(acac)₃ doping concentration is 0.1 mg / mL. Furthermore, no other impurity phase peaks appeared outside the background diffraction peaks, indicating that the addition of Cr(acac)₃ did not alter the crystal structure and phase composition of the CsPbI₂Br perovskite. This shift occurs due to the smaller Cd₂ content. 3+ Ions were successfully incorporated into the CsPbI₂Br lattice, partially replacing Pb. 2+ This leads to lattice contraction and increases the diffraction angle. Due to acac... − The ionic radius (340 pm) is much larger than that of Br. − The ionic radius (169 pm) and I − The ionic radius (220 pm), acac − More likely to be present at perovskite grain boundaries with Pb 2+ The Cr(acac)3 additive, rather than being incorporated into the CsPbI2Br lattice, regulates the crystallization process of the CsPbI2Br perovskite through both ion coordination and grain boundary doping, resulting in a high-quality perovskite film.
[0049] It is well known that the quality and morphology of perovskite films play equally important roles in improving PCE (Potentially Specific Emissions). To investigate the effect of Cr(acac)3 on the microstructure of perovskite films, CsPbI2Br films and CsPbI2Br films with added Cr(acac)3 were characterized by SEM, such as... Figure 3 (Comparative example) and Figure 4 As shown in (Example 2). From Figure 3 The surface morphology of the CsPbI₂Br film reveals that the perovskite film exhibits significant grain boundaries and pores, with small and loosely arranged grains. This leads to decreased device efficiency and causes interfacial charge accumulation and energy loss. In contrast, the CsPbI₂Br film with added Cr(acac)₃... Figure 4In this process, the perovskite grains are significantly larger, the grain boundaries are fewer, and the grain arrangement is more compact, all of which are beneficial for improving photovoltaic performance. Combined XRD and SEM results show that the addition of Cr(acac)3 significantly improves the crystallinity of the CsPbI2Br film, forming a high-quality perovskite film. This can be attributed to the presence of acac in Cr(acac)3. − Aggregates at the grain boundaries of CsPbI2Br and interacts with uncoordinated Pb in the perovskite. 2+ Bonding, Cr 3+ Pb is partially substituted into the lattice of CsPbI2Br. 2+ This regulates perovskite crystal growth and promotes the formation of high-quality CsPbI2Br perovskite films.
[0050] To investigate whether Cr(acac)3 was successfully added into the CsPbI2Br perovskite light-absorbing layer, energy dispersive spectroscopy (EDS) was used for testing. Figure 5 The results of (Example 2) also clearly show that Cr is uniformly dispersed in the CsPbI₂Br perovskite, confirming the successful addition of Cr(acac)₃. To further investigate the effect of Cr(acac)₃ addition on the elemental state in the CsPbI₂Br perovskite film, XPS measurements were performed. Figure 2 As shown in Comparative Example and Example 2, compared with Cr(acac)3, the O 1s orbital binding energy of the perovskite film after the addition of Cr(acac)3 shifts to higher energy levels, from 529.75 eV and 531.46 eV to 530.83 eV and 532.25 eV, indicating that the acac in Cr(acac)3... − Pb uncoordinated with perovskite surface and grain boundaries 2+ The bonding, forming a highly covalent Pb-O bond, leads to a decrease in the electron cloud density around the oxygen atom, thus passivating defects. Figure 2 The diagram shows the changes in binding energies of the CsPbI2Br core elements before and after the addition of Cr(acac)3. The binding energy peaks of Pb 4f, Cs 3d, I 3d, and Br 3d all shifted towards higher binding energies. Specifically, the peak position of Pb 4f shifted from 137.57 eV and 142.43 eV to 137.69 eV and 142.55 eV, indicating that the binding energy of acac... − With uncoordinated Pb 2+ The interaction between them further demonstrates that acac − With Pb 2+ Bonding occurs at the perovskite surface and grain boundaries, with electron density redistributing towards the Pb-O bond region; while the peak positions of Cs 3d shift from 723.84 eV and 737.78 eV to 723.95 eV and 737.89 eV, attributed to the partial encapsulation of Cs.+ Pb 2+ Cr, which has a strong electronegativity 3+ Replacement, leading to Cs + The increased electron density further confirms the presence of Cr in Cr(acac)3. 3+ It successfully entered the CsPbI₂Br lattice and interacted. Furthermore, both I₃d and Br₃d directions shifted towards higher binding energies, moving from 618.42 eV and 67.65 eV to 628.42 eV and 67.75 eV, respectively. Previous studies have shown that when Cr₂Br has a smaller radius and higher electronegativity... 3+ When an ion enters the PbX6 octahedral structure of the perovskite lattice, it alters the electron cloud density around adjacent halide ions. This results in a slight increase in the binding energy between the nucleus and its electrons, causing the overall binding energy to shift to higher values.
[0051] To more fully investigate the effect of adding Ca(acac)3 on the optoelectronic performance of the device, JV curve tests were performed on PSCs with different concentrations of Ca(acac)3. Figure 6 (Comparative Examples and Examples 1, 2, and 3) and Table 1 show the JV curves and photoelectric performance data of the corresponding devices. It can be seen that the addition of Ca(acac)3 to the perovskite significantly improves the photoelectric performance of the perovskite devices. When the concentration of Ca(acac)3 is 0.1 mg / mL, the device achieves a maximum PCE of 14.21%, significantly higher than the 12.50% of the control device. V OC Increase from 1.18 V to 1.22 V. J SC From 13.66 mA / cm 2 Increased to 14.83 mA / cm 2 FF increased from 77.15% to 78.15%. Figure 7 (Comparative Example and Example 2) shows the EQE spectra and corresponding integrated current densities of the control device and the device with added Ca(acac)3. The EQE of the device with added Ca(acac)3 is higher than that of the control device, and the integrated current densities of the control device and the device with added Ca(acac)3 are 13.38 mA / cm², respectively. 2 and 14.14 mA / cm 2 This value is the same as that obtained from the JV curve. J SC The value error is less than 5%, indicating a good degree of agreement.
[0052] In order to study the reproducibility of the device, Figure 8 and Figure 9(Comparative Examples and Examples 1, 2, and 3) and Table 2 present the photovoltaic parameter statistics box plots and statistical data for 20 independent PSCs with different concentrations of Ca(acac)3. It can be seen that all sample parameters exhibit a narrow statistical distribution range, indicating good reproducibility of the device fabrication process. This further demonstrates that the introduction of Ca(acac)3 is beneficial for improving the PCE of the device.
[0053] Figure 10 (Comparative Example and Example 2) shows the stable current output and stable efficiency output of the control device and the device after adding Ca(acac)3. Under a bias voltage of 0.98 V, the photocurrent density of the device after adding Ca(acac)3 is 14.20 mA / cm². 2 The control device, at a bias of 0.91 V, provided only 13.30 mA / cm². 2 The photocurrent density was [not specified]. Furthermore, after 400 s of continuous illumination with the addition of Ca(acac)3, the device showed no significant decrease in stable current output and stable efficiency output curves, demonstrating good illumination stability.
[0054] Furthermore, to further evaluate the stability of PSCs, the storage performance of unencapsulated PSCs was investigated in ambient air with a humidity (RH) of 15–20%, such as… Figure 11 (Comparative Example and Example 2). According to the normalized PCE versus measurement time curve, the perovskite device with added Ca(acac)3 retained 92% of its initial PCE after 40 days of storage at room temperature, while the control device only retained 64% of its initial PCE. This demonstrates that adding Ca(acac)3 can effectively improve the stability of PSCs.
[0055] Table 1. JV curve parameters of PSCs after adding different concentrations of Cr(acac)3 <![CDATA[without Cr(acac)3]]> 1.18 13.66 77.15 12.50 <![CDATA[Cr(acac)3(0.05 mg / mL)]]> 1.21 14.72 75.26 13.44 <![CDATA[Cr(acac)3(0.10 mg / mL)]]> 1.22 14.83 78.45 14.21 <![CDATA[Cr(acac)3(0.15 mg / mL)]]> 1.21 14.64 76.98 13.67 Table 2. Statistical analysis of photovoltaic parameters of devices after adding different concentrations of Cr(acac)3. <![CDATA[Cr(acac)3-free]]> 1.17±0.04 13.82±0.73 74.56±3.24 12.03±0.70 <![CDATA[0.05mg / mL Cr(acac)3]]> 1.19±0.02 14.57±0.51 75.79±2.31 13.20±0.25 <![CDATA[0.10mg / mL Cr(acac)3]]> 1.22±0.04 14.69±0.62 77.06±2.20 13.93±0.39 <![CDATA[0.15mg / mL Cr(acac)3]]> 1.22±0.04 14.61±0.39 76.40±2.05 13.56±0.23 As explained above, compared to the undoped blank control, this invention uses Cr(acac)3 After doping modification, the performance of devices in all doped experimental groups was significantly improved. The optimal doping concentration was 0.10 mg / mL, achieving a synergistic optimal effect of lattice defect repair, grain boundary passivation, and interface energy level modulation, while balancing thin film crystal quality, carrier transport efficiency, and long-term device stability. Insufficient doping resulted in inadequate defect passivation, while excessive doping easily led to component accumulation and hindered charge transport, further validating the rationality of the technical solution and the innovativeness of the parameter range in this invention.
Claims
1. A method for preparing high-performance CsPbI2Br perovskite solar cells, characterized in that, Includes the following steps: S1, TiO2 electron transport layer preparation: TiO2 precursor solution was prepared by dissolving titanium tetrachloride in deionized water under ice bath conditions; After cleaning and UV ozone treatment, FTO glass is immersed in TiO2 precursor solution, deposited at constant temperature, and annealed to obtain TiO2 electron transport layer. S2. Preparation of the perovskite light-absorbing layer: Prepare a Cr(acac)3 and DMSO modified solution, add PbBr2, PbI3 and CsI, stir until clear, and obtain a modified perovskite precursor solution; The modified perovskite precursor solution was preheated and then spin-coated onto the TiO2 electron transport layer using a two-step spin-coating process. Cr(acac)3-doped CsPbI2Br perovskite films were prepared by pre-annealing and high-temperature annealing. S3. Carbon electrode preparation: Carbon paste is coated onto the surface of a Cr(acac)3-doped CsPbI2Br perovskite thin film using a screen printing process, and then cured by heating to complete the preparation of the CsPbI2Br perovskite solar cell.
2. The method for preparing high-performance CsPbI₂Br perovskite solar cells according to claim 1, characterized in that, In step S1, the volume ratio of titanium tetrachloride to deionized water is 9:400; The FTO conductive glass was cleaned with detergent during the cleaning process. Then, the cleaned FTO conductive glass was placed in distilled water and ethanol for ultrasonic cleaning for 20-30 minutes each, and then dried at 60℃ for 30 minutes. During the ultraviolet ozone treatment of FTO glass: the intensity of ultraviolet light is 0.4mW / cm², ozone cleaning is performed under ultraviolet light irradiation, and the ozone cleaning time is 15-25 minutes.
3. The method for preparing high-performance CsPbI₂Br perovskite solar cells according to claim 1, characterized in that, In step S1, the temperature for immersing the FTO glass in the TiO2 precursor solution for deposition is 60-80℃, and the deposition time is 20-40 min. The annealing time is 60-90 minutes, and the annealing temperature is 180-220℃.
4. The method for preparing high-performance CsPbI₂Br perovskite solar cells according to claim 1, characterized in that, In step S2, the concentrations of Cr(acac)3 and DMSO modified solutions are 0.05 mg / mL to 0.15 mg / mL.
5. The method for preparing high-performance CsPbI₂Br perovskite solar cells according to claim 1, characterized in that, In step S2, the solid-liquid ratio of DMSO, PbBr2, PbI, and CsI in the modified perovskite precursor solution is 100mL:22g:28g:31g.
6. The method for preparing high-performance CsPbI₂Br perovskite solar cells according to claim 1, characterized in that, In step S2, the preheating temperature of the modified perovskite precursor solution is 60℃. The two-step spin coating process is as follows: the TiO2 electron transport layer is placed on a spin coater, and the preheated modified perovskite precursor solution is spin-coated onto the TiO2 electron transport layer using a pipette; spin coating is performed at 700 rpm for 5 seconds and at 4000 rpm for 35 seconds. 47 μL of modified perovskite precursor solution was used for a 1 cm * 1 cm TiO2 electron transport layer.
7. The method for preparing high-performance CsPbI₂Br perovskite solar cells according to claim 1, characterized in that, In step S2, the pre-annealing temperature is 36-40℃ and the pre-annealing time is 70-90s; The high-temperature annealing temperature is 160-200℃, and the high-temperature annealing time is 5-15 minutes.
8. The method for preparing high-performance CsPbI₂Br perovskite solar cells according to claim 1, characterized in that, The screen printing process in step S3 is as follows: carbon paste is coated onto the surface of a highly Cr(acac)3-doped CsPbI2Br perovskite thin film by screen printing, and then heated on a heating stage at 110-140℃ for 10-20 minutes to complete the fabrication of CsPbI2Br perovskite solar cells.
9. The method for preparing a high-performance CsPbI₂Br perovskite solar cell according to claim 1, characterized in that, The solid content of the carbon slurry in step S3 is 50 wt%; The coating thickness of carbon paste on the surface of highly Cr(acac)3-doped CsPbI2Br perovskite thin films was controlled at 8-10 μm.
10. The method for preparing a high-performance CsPbI₂Br perovskite solar cell according to claim 8, characterized in that, In step S3, carbon paste is screen-printed onto the surface of a highly Cr(acac)3-doped CsPbI2Br perovskite film and heated on a heating stage at 120°C for 15 minutes.